ANALISIS KOMPOSISI KIMIA DAN SIFAT ORGANOLEPTIK TEPUNG PISANG Ã¢â‚¬Å“MULU BEBEÃ¢â‚¬Â (Musa acuminata) DENGAN SUHU DAN WAKTU PENGERINGAN YANG BERBEDA - Ibrahim, Abu Rahmat; Albaar, Nurjanna (Cannarium, 2020)
The present study aims to analyze the effect of temperature and drying time on chemical composition and organoleptic characteristics of "Mulu bebe" banana flour. The experiment was established using a completely randomized design (CRD) within a factorial arrangement with each treatment had three replications. The combination of treatments include: 5 hours drying time at 35Ã¢ÂÂ°C (S1s1), 10 hours drying time at 35Ã¢ÂÂ°C (S1s2), 15 hours drying time at 35Ã¢ÂÂ°C (S1s3), 5 hours at 40Ã¢ÂÂ°C (S2s1), 10 hours drying time at 40Ã¢ÂÂ°C (S2s2), 15 hours drying time at 40Ã¢ÂÂ°C (S2s3), 5 hours drying time at 45Ã¢ÂÂ°C (S3s1), 10 hours drying time at 450C (S3s2) and 15 hours drying time at 45Ã¢ÂÂ°C (S3s3). The parameters observed were chemical composition (water, carbohydrates, fiber, fat and protein) and organoleptic properties (color, texture and odor). The results showed that the chemical and organoleptic properties had been significantly affected by drying time and temperature. The best chemical properties of "Mulu bebe" banana flour was found at the drying time of 15 hours at 45Ã¢ÂÂ°C, while the organoleptic properties have a positive correlation with chemical composition.